The capacity to be displaced : resilience, mission, and inner strength - Sedmak, Clemens, 1971- (Theology and Mission in World Christianity, 2017)
The experience of displacement is shared by people who work internationally. The capacity to be displaced is a necessary strength and skill for people working across cultures, particularly for missionaries. In order to deal with the stressful nature of displacement people need to be resilient, resilience makes people flourish in adverse circumstances. This volume presents a specific type of resilience, namely "resilience nourished by inner sources." Cultivating inner resilience draws on all the facets of a person's interior life: thoughts and memories, hopes and desires, beliefs and convictions, concerns and emotions. The notion of inner strength and resilience from within is developed using many examples from missionaries and development workers as well as case studies from all over the world.